PENGEMBANGAN MEDIA ENGKLEK KERJASAMA (ENGKER) BERBASIS PENDIDIKAN KARAKTER DALAM MUATAN PPKN KELAS IV SEKOLAH DASAR - Cica Purwanti; Waluyo Hadi; Nina Nurhasanah (Universitas Trilogi, 2022)
The research and development aims to produce learning media for Pancasila and Civic Education in the form of a traditional game of engklek, called Engklek Kerjasama (ENGKER) and to test the feasibility of the developed learning media. In addition, this media is to introduce the value of cooperative character to students. The development model used by researcher is ADDIE (Analyze, Design, Development, Implementation and Evaluation. Respondents in this research and development consisted of class IV elementary school teacher and 16 grade IV students elementary school. Sources of data were obtained from interviews and questionnaires. Furthermore, it is analyzed using qualitative an quantitative analysis techniques. The result of the validation obtained an average value of 97,67% by media experts at 98.52%, the material expert at 96.42%, and the linguist at 98.07%. Furthermore, the product assessment of grade IV elementary school teachers was 98.07%. Then, based on the results of students trials, it was obtained an average value of 93,8% for the one to one stage of 92.5%, the small group stage of 94.86%, and the field test stage of 94.27%. This shows that this media belongs in the very good category, therefore it is appropriate to be used as a learning media for Pancasila and Civic Education for Class IV elementary school especially the material of cooperation in diversity.